Covalently Tethered Polyoxometalate–Pyrene Hybrids for Noncovalent Sidewall Functionalization of Single‐Walled Carbon Nanotubes as High‐Performance Anode Material. (8th July 2013) - Ma, Dui; Liang, Liying; Chen, Wei; Liu, Haimei; Song, Yu‐Fei
Abstract A covalently tethered polyoxometalate (POM)–pyrene hybrid (Py–SiW11) is utilized for the noncovalent functionalization of single‐walled carbon nanotubes (SWNTs). The resulting SWNTs/Py–SiW11 nanocomposite shows that both SiW11 and pyrene moieties could interact with SWNTs without causing any chemical decomposition. When used as anode material in lithium‐ion batteries, the SWNTs/Py–SiW11 nanocomposite exhibits higher discharge capacities, and better rate capacity and cycling stability than the individual components. When the current density is 0.5 mA cm−2, the nanocomposite exhibits the initial discharge capacity of 1569.8 mAh g−1, and a high discharge capacity of 580 mAh g−1 for up to 100 cycles.